"FACTORS INFLUENCING CAREER SUCCESS OF FACULTY IN CHINESE PRIVATE UNIVERSITIES: A SOCIAL COGNITIVE CAREER THEORY (SCCT) PERSPECTIVE" - Zeng , Chunlong; Saufi, Roselina Ahmad (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study investigates factors influencing faculty career success in Chinese private universities through the lens of Social Cognitive Career Theory (SCCT). Quantitative and sequential mixed-methods data from 152 faculty across three provinces reveal that self-efficacy beliefs and outcome expectations significantly predict career success (β = .33, p<.001). However, policy instability catastrophically mediates this relationship, weakening the efficacy-success link by 72% when promotion criteria frequently change. Qualitative analysis of 18 dissonant cases identifies three adaptation archetypes: "Stealth Researchers" (embedding scholarship in teaching, 42%), "Compliance Pivots" (abandoning core research for institutional priorities, 33%), and "Exit Preparers" (seeking public-sector roles, 25%). The research critically expands SCCT’s environmental dimension, demonstrating how market-driven precarity transforms "support" into fluid constructs like peer networks and workload flexibility. Findings urge institutional reforms prioritizing policy consistency, mental health support, and strategic resource allocation to mitigate talent attrition in China’s commercialized higher education sector.